Climate laws in small European states: symbolic legislation and limits of diffusion in Ireland and Finland. Issue 6 (19th September 2019) - Torney, Diarmuid
ABSTRACT: The past decade has seen the introduction of framework climate change laws in several countries. The development of climate laws in two small European states, Ireland and Finland, both of which introduced national climate laws in 2015, are examined. Two questions are addressed. First, to what extent do later adopters of climate policy instruments draw on the examples of pioneering legislation? Second, how and why are pioneering climate policy instruments modified by later adopters? In both cases, the 2008 UK Climate Change Act was a source of inspiration in the early stages, particularly for civil society campaigns. Thereafter, domestic interests mobilised to remove from legislative proposals the most pioneering and ambitious parts of the UK model. The result, in both cases, was enactment of climate laws that resembled only very loosely the UK Climate Change Act.